Effectiveness of Mindfulness-based Cognitive Therapy (MBCT) on Martial Adjustment among Women - Shahrbanoo Ghahari (Journal of Global Pharma Technology, 2017)
Background and goal: marital adjustment is one of the most important issues has been considered in societies. Mindfulness-based cognitive therapy is an effective method in increase of marital adjustment; hence, the purpose of this study is to determine effectiveness of mindfulness-based cognitive therapy on marital adjustment among women. Materials and method: the plan of research is experimental with type of pretest and posttest with control group. Statistical population of this study included all persons who had referred to two Counseling Centers in Rasht City, Iran in 2015. Qualified persons to enter into the study filled out Dyadic Adjustment Scale (DAS) and 30 members were randomly chosen out of 50 members who had gained the lower score than cut off point of marital adjustment (100) and then placed into two test and control groups. Experimental intervention (mindfulness-based cognitive therapy) was implemented on test group and post test was conducted for both groups after the end of intervention. The obtained data from Multivariate Analysis of Covariance (MANCOVA) were analyzed through SPSS 22 software. Findings: The obtained results indicated mindfulness training had a significant effect on marital adjustment among women (P<0/01).Conclusion: according to the obtained results, it can be stated that mindfulness-based cognitive therapy would lead to increase in marital adjustment of women.